"All Teaching Should Be Integration": Social Studies and Literacy Integration in Preservice Teacher Education. Issue 6 (2nd November 2019) - Shifflet, Rena; Hunt, Carolyn S.
Abstract: The absence of social studies curriculum is a problem because it undermines the essential purposes of schooling: to prepare participatory, contributing members of a democratic society. In this article, we argue that integrating the literacy and social studies curricula is one meaningful way to support such civic-minded social studies instruction in elementary classrooms. As 2 teacher educators working with teacher candidates placed in their final clinical before student teaching, we saw the potential to model meaningful integration in literacy and social studies. In this 2-year qualitative study, we highlight how 14 teacher candidates engaged in the integration of literacy and social studies during their yearlong placement in a professional development school program and what factors influence their implementation of integration. Findings from this study revealed that effective integration required a strong vision of the complexities of integration and the importance of intentional planning. To get past the constraints of traditional compartmentalized scheduling, teacher candidates needed high-quality modeling of integration within their clinical placement. We offer implications for teacher educators and school/university partnerships.